Syntheses and applications of furanyl-functionalised 2,2’:6’,2’’-terpyridines - Husson, Jérôme; Knorr, Michael (Beilstein Journal of Organic Chemistry, 2012)
Different synthetic routes leading to terpyridines functionalised with furan heterocycles are reviewed. The methodologies used to prepare such compounds include the ring closure of 1,5-diketones and cross-coupling reactions. These versatile terpyridines and their derived metal complexes find applications in various fields including coordination chemistry, medicinal chemistry and material sciences.
Keywords: chelate complexes; furan; heterocycles; oligopyridines; terpyridine